Seats for shop assistants act, 1899, and sale of food and drugs act, 1899. Notes and explanations on the undermentioned acts of parliament (Co-operative Union, 1899)
Iss. for the guidance of the Committees of Co-operative Societies by the Joint Parliamentary Societies by the Joint Parliamentary Committee of the Co-operative Union and Co-operative Wholesale Societies.